Contribution of Acacia mangium Root Systems to Slope Stability Improvement - Maneekeaw, Siriphat; Voottipruex, Panich; Kongsomsaksakul, Sirisak; Sramoon, Wilailak; Mahannopkul, Krairoj (Salehan Institute of Higher Education, 2026)
This study explores the bioengineering potential of Acacia mangium root systems in enhancing the shear strength of lateritic soil under both saturated and unsaturated conditions. Seedlings were cultivated in cylindrical containers for 12 months to monitor root growth and investigate its relationship with key geotechnical parameters. Root development was classified into three distinct phases: root acceleration (months 1–3), stem acceleration (months 4–8), and growth phase (months 9–12). A significant dry root biomass increase was observed, exhibiting a strong linear correlation with peak shear strength. Laboratory shear tests indicated that unreinforced soil in saturated conditions had a cohesion of 1.90 kPa and an internal friction angle of 27.64°. In contrast, cohesion increased to 3.55 kPa in unsaturated conditions and the internal friction angle to 38.94°. In comparison, root-reinforced soils demonstrated substantially improved shear strength. Under unsaturated conditions, cohesion and internal friction angle reached 9.92 kPa and 41.58°, respectively, while in saturated conditions, values increased to 6.12 kPa and 31.29°. Slope stability analysis using Slope/W software revealed that the unreinforced slope had a Factor of Safety (FS) of 1.043, indicating marginal stability. However, with A. mangium root reinforcement, the FS increased to 1.518, exceeding the commonly accepted safety threshold of 1.5. These results highlight the effectiveness of A. mangium root systems in improving slope stability through mechanical reinforcement, increased soil cohesion, and redistribution of shear stresses within the soil matrix.